Vrouwelijke muziekmecenassen in de Republiek der Nederlanden - Amerongen, Veronica van (Amsterdam Amsterdam University Press, 2023)
The influence of women on musical life in the Dutch Republic (1579-1795) is much greater than has always been assumed so far. Indeed, women played a substantial role in supporting musicians through money or protection. Music historian Veronica van Amerongen discovered this by researching commissioned scores, subscription lists to musical pieces and payment for organs and chimes, among other things. It is noteworthy that women acted as patrons, because at that time they were not officially empowered to act and thus depended on relatives for financial expenditure.Patronage was mainly associated with stadholder courts, wealthy women and the nobility. Stadholder's wives (from abroad) in particular played an important part in fostering a regal musical life. 'Winter Queen' Elizabeth Stuart (1595-1662) and the musical stadholder's wife Anna of Hanover (1709-1759) set the tone in this respect.
Keywords: 16th Century (1501-1600); 17th Century (1601-1700); 18th Century (1701-1800); Music history; Patronage; Female; Organ; Bell; Netherlands